(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In recent decades, and to this day computer technology has been used in applications and various fields including the medical field, which prompted many researchers to employ this technique in the design of decision support systems using many of the algorithms and methods for this purpose. In this paper, k-means and back propagation are proposed to classify medical datasets and then compare the performance of these methods, practical experiments show back propagation has best results than k-means.